Determinants of Eastern Indonesia's Human Development Index - Jatmiko Wahyu Nugroho; Nurjanna Ladjin; Erwin Agus; Suwardi Zakaria; Iwan Harsono (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to determine the underlying Human Development Index in Eastern Indonesia Region by using Health expenditure and Education expenditure as variables that affect it. Using a new numerical perspective where the measurement of the Human Development Index according to the UNDP is reviewed by tracing and analysing Health and Education expenditure data using panel data, namely cross-section and time series to see the effect statistically. The results of this study which obtained positive and insignificant numbers and the low contribution value of the influence variables in this study are challenging data to face global progress, various forms of access to social services, especially in health and education, are basic things that need to be considered, some regions included in Eastern Indonesia may have experienced progress, but equity itself is what we must pay attention to together, continuous efforts to overcome the challenges of progress must ensure that all Indonesians can enjoy prosperity.